Gambaran Ide Bunuh Diri pada Mahasiswa di Kota Bandung - Aleyda Atqiya; Farida Coralia (Bandung Conference Series: Psychology Science, 2023)
Abstract. College students are one of the populations that have a risk of suicide. As a first step towards suicide attempts and actual suicide, suicidal ideation is considered a significant predictor of suicide attempts and suicide. College students experience higher levels of suicidal ideation than those experienced by young adults of the same age in the community. Burdens and problems that arise during college can affect mental health associated with an increased risk of suicide. This study aims to obtain empirical data regarding the description of suicidal ideation among students in the city of Bandung. Data was collected using the Scale for Suicide Ideation (SSI) measuring instrument. The subjects of this study were active university students in the city of Bandung who had 89 suicide ideas. The results of this study indicate that students in the city of Bandung have low suicide ideation (68.5%). Female students had a higher score of suicidal ideation (mean = 13.57) compared to male students (mean = 11.84). The fourth year of study had the highest suicide ideation score (mean=13.20). Problems in the family are the majority of the triggers for suicidal ideation among students in the city of Bandung. Abstrak. Mahasiswa merupakan salah satu populasi yang memiliki resiko bunuh diri. Sebagai langkah pertama menuju upaya bunuh diri dan tindakan bunuh diri sebenarnya, ide bunuh diri dianggap sebagai prediktor signifikan dari upaya bunuh diri dan tindakan bunuh diri. Tingkat keinginan bunuh diri yang dialami mahasiswa lebih tinggi daripada yang dialami oleh orang dewasa muda seusianya di masyarakat. Beban dan permasalahan yang muncul pada masa perkuliahan dapat mempengaruhi kesehatan mental terkait dengan peningkatan resiko bunuh diri. Tujuan dari penelitian ini untuk memperoleh data empiris mengenai gambaran ide bunuh diri pada Mahasiswa di Kota Bandung. Pengumpulan data dilakukan dengan menggunakan alat ukur Scale for Suicide Ideation (SSI). Subjek penelitian ini adalah mahasiswa aktif perguruan tinggi di Kota Bandung yang memiliki ide bunuh diri sebanyak 89 orang. Hasil penelitian ini menunjukan bahwa mahasiswa di Kota Bandung memiliki ide bunuh diri yang rendah (68.5). Mahasiswa perempuan memiliki skor ide bunuh diri yang lebih tinggi (mean= 13.57) dibandingkan dengan mahasiswa laki laki (mean= 11.84). Tahun studi keempat memiliki skor ide bunuh diri yang paling tinggi (mean= 13.20). Permasalahan dalam keluarga merupakan mayoritas pemicu ide bunuh diri pada mahasiswa di Kota Bandung.